Self-initiated expatriation: A "new" management challenge. An analysis based on bibliometrics - Carolina Machado (Administrative Sciences, 2022)
The globalization movement, the growing processes of internationalization and opening of markets that have been observed over recent decades have brought with them a significant increase in cross-border movements, with expatriation assuming a prominent role. However, if expatriation is a reality of international markets, over recent years, this concept has taken on different typologies, including self-initiated expatriation. Characterized by the individual initiative that encourages individuals to move beyond their national borders in search of an international work experience, it is critical to understand the phenomena related to SIE. More precisely, we aim to study the problematics of SIE, namely, when it started to be studied and who has published in this area of research, and the identification of the main types/sources of publication used to disseminate these works, as well as the main topics that, within the scope of SIE, have been studied. To answer these questions, using information taken from the Scopus database, a qualitative study of an interpretive nature based on bibliometric analysis was performed. At first, in order to better understand the phenomenon of expatriation in global terms, 1050 publications were obtained using the item 'expatriation'. In a second step, in order to answer the questions posed, the key item of the research focused on the concept 'self-initiated expatriation', with 82 publications identified. The obtained results allowed us to conclude, among other observations, that although the phenomenon of expatriation has been studied for many years, the particular case of SIE began to gain greater prominence from 2010 onwards, with the highest peak in the number of publications observed in the period between 2012 and 2014. The top five main authors who are working in this field, the main sources where these publications (mostly scientific articles) are most frequently published, the main countries of origin, and the main approaches developed by the different authors are highlighted here. Theoretical and practical contributions, as well as the political implications of this study, are highlighted in order to encourage the development of more exhaustive studies of SIE, thus contributing to the promotion of policies and practices oriented towards the management of SIE, which can explore the potential skills that these individuals have more deeply and thus contribute to the greater and more effective development of the companies and economies of the countries that host them.
Keywords: 350; bibliometric analysis; cross-cultural movements; expatriation; management; publications; self-initiated expatriation